2012 American Control Conference (ACC) 2012
DOI: 10.1109/acc.2012.6315164
|View full text |Cite
|
Sign up to set email alerts
|

Output-feedback control of nonlinear bilateral teleoperators

Abstract: The output-feedback design problem for a bilateral teleoperator scheme is considered. The recently proposed Immersion and Invariance (I&I) observer is used to obtain an exponentially convergent estimate of the unmeasured velocities. Moreover, it is proven that when this observer is interconnected to the nonlinear teleoperator together with a Proportional plus damping (P+d) controller, the overall system is globally stable. Finally, in the case when the human operator and the environment do not exert forces on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Future research includes the design of velocity observers together with position tracking controllers to give a solution to the teleoperators control when joint velocities are not measurable and will also include an evaluation of performance of the proposed schemes, see [18] for a solution to the observercontroller case for rigid manipulators. …”
Section: Discussionmentioning
confidence: 99%
“…Future research includes the design of velocity observers together with position tracking controllers to give a solution to the teleoperators control when joint velocities are not measurable and will also include an evaluation of performance of the proposed schemes, see [18] for a solution to the observercontroller case for rigid manipulators. …”
Section: Discussionmentioning
confidence: 99%
“…In order to relax the restrictive requirement for full state measurements in designing the controllers in the existing results, some efforts on partial state feedback control have been made. To estimate the unmeasurable velocity, observers are constructed by invoking the Immersion and Invariance (I&I) techniques [8][9][10]. Through introducing two extra states, some lower dimensional observer is proposed in [9] in comparison to that in [8], and moreover, the explicit expressions of the observer have been given.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting (17) in (27), with the fact that, for r > 0, r−1 r ≤ 1, and the previous bounds, with α = b B 2 , yieldṡ…”
Section: Propositionmentioning
confidence: 99%
“…Moreover, it is also shown that, if the human operator and the environment do not exert any forces on the local and remote manipulators then position error and velocities asymptotically converge to zero; 3) the design, different from previous works, in particular to [27], of a velocity observer for general nonlinear manipulators interconnected with a communication channel that can induce variable time-delays. Up to the authors knowledge, this is among the first works that can guarantee position tracking capabilities in bilateral teleoperators that are not equipped with velocity sensors and that exhibit variable time-delays in the communication channel.…”
Section: Introductionmentioning
confidence: 99%